Tanshinone IIA Exerts Anti-Inflammatory and Immune-Regulating Effects on Vulnerable Atherosclerotic Plaque Partially via the TLR4/MyD88/NF-κB Signal Pathway - Chen, Zhuo; Gao, Xiang; Jiao, Yang; Qiu, Yu; Wang, Anlu; Yu, Meili; Che, Fangyuan; Li, Siming; Liu, Jing; Li, Jingen; Zhang, He; Yu, Changan; et al. (Frontiers in Pharmacology, 2019)
Background— Tanshinone IIA (Tan IIA), a lipophilic constituent from Salvia miltiorrhiza Bunge, has shown a promising cardioprotective effect including anti-atherosclerosis. This study aims at exploring Tan IIA’s anti-inflammatory and immune-regulating roles in stabilizing vulnerable atherosclerotic plaque in ApoE deficient (ApoE-/-) mice. Methods— Male ApoE-/- mice (6 weeks) were fed with high fat diet for 13 weeks and then randomized to model group (MOD) or Tan IIA groups [high dose: 90 mg/kg/day (HT), moderate dose: 30 mg/kg/day (MT), low dose: 10 mg/kg/day (LT)] or atorvastatin group (5mg/kg/day, ATO) for 13 weeks. Male C57BL/6 mice (6 weeks) were fed with ordinary rodent chow as control. The plaque stability was evaluated according to the morphology and composition of aortic atherosclerotic (AS) plaque in H&E staining and Movat staining sections by calculating the area of extracellular lipid, collagenous fiber and foam cells to the plaque. The expression of Toll-like receptor 4 (TLR4)/ myeloid differentiation factor88 (MyD88)/ nuclear factor-kappa B (NF-κB) signal pathway in aorta fractions was determined by immunohistochemistry. Serum level of blood lipid were measured by turbidimetric inhibition immunoassay. The concentrations of tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) were detected by cytometric bead array. Results— Tan ⅡA stabilized aortic plaque with a striking reduction in the area of extracellular lipid (ATO: 13.15±1.2%, HT: 12.2±1.64%, MT: 13.93±1.59%, MOD: 18.84±1.46%, P<0.05) or foam cells (ATO: 16.05±1.26%, HT: 14.88±1.79%, MT: 16.61±1.47%, MOD: 22.08±1.69%, P<0.05) to the plaque, and an evident increase in content of collagenous fiber (ATO: 16.22±1.91%, HT: 17.58±1.33%, MT: 15.71±2.26%, LT:14.92±1.65%, MOD: 9.61±0.7%, P<0.05) to the plaque than that in the model group, concomitant with down-regulation of the protein expression of TLR4, MyD88 and NF-κB p65, and serum level of MCP-1, TNF-α in a dose-dependent manner. There were no differences in serum TC, LDL, HDL or TG levels between ApoE–/– mice and that treated with atorvastatin.Conclusions—These results suggest Tan IIA could stabilize vulnerable AS plaque in ApoE-/- mice and this anti-inflammatory and immune-regulating effect may been achieved via TLR4/MyD88/NF-κB signaling pathway.